Caracterização microbiológica, fermentativa e estabilidade aeróbia em silagens pré-secadas de capim Tifton 85, com diferentes camadas de filme de polietileno e tempos de armazenamento - Nath, Caroline Daiane (2016)
This work aimed to evaluate the microbiological and fermentative profile, aerobic stability and variation of the external temperature in silo bags with pre-dried silage of Tifton 85 grass, with different layers of polyethylene film and storage times. The trial design was completely randomized with a split plot in the weather, with 4 replications. In the main plot were allocated the treatments (2 and 3 layers of involvement) and the subplots the sampling times, 3 times (30, 60 and 90 days of storage) for microbiological and fermentative evaluation and water activity (Aw) and 5 times (0, 1, 2, 3 and 4 days of aerobic exposure) for aerobic stability evaluation. For the study of the external temperature variation in silos during storage, the treatment allocated in the plots were constituted by evaluation strata (surface, middle and silo base) and the subplots, the evaluation times (0, 7, 14, 21, 28, 35, 42, 49, 56, 63, 70, 77 and 84 days of storage). Silos of 400 kg have been made, with the use of inoculant in the baling and these ones stored in the weather, and after their opening were placed in a covered shed. In the microbiological profile, after the silage s opening, it was quantified by culturing, the population of Clostridium, Bacillus, enterobacteriaceae, lactic acid bacteria, Listeria sp., Salmonella sp., yeasts and fungi. The aerobic stability was evaluated from its opening to the fourth day of exposure of the silage to the oxygen. The pH and the levels of soluble carbohydrates and ammonia nitrogen (NH3/ N total) were evaluated after the silage s opening. The evaluation of temperature in the silo strata (surface, middle and base) was performed weekly during the silage s storage, with the aid of an infrared thermometer with laser sight. It was found that the storage time and the number of layers of polyethylene film has not reflected in changes in the Clostridium population, lactic acid bacteria and Aw. values. There was a decrease in the population of enterobacteria with the increasing of storage period in both treatments. The Bacillus population was lower in silages made with three layers of involvement (3.63 log CFU g-1), 30 days of opening. There was no growth of Listeria sp. and Salmonella sp. during the silage storage period. The fungus genre of greater occurrence in silage pre-dried of Tifton 85 grass was the Penicillium. There was no breach of aerobic stability during periods of evaluation due to the high temperatures of silage, which are above ambient temperature. The pH was greater than recommended for good silage preservation (4.2) in the opening and during exposure to oxygen. It was found that the content of ammonia nitrogen and soluble carbohydrates in the silages with two layers differ between the storage times. There was alteration in temperature in the different strata of evaluation in silos with two layers of involvement at 0, 7, 14, 21, 28, 35 and 42 days and the silos with three layers of involvement at 0, 7, 14, 21 and 35 days of storage. The temperature at the base and in the middle of the silos with two and three layers of involvement at 0, 7, 14, 21, 28, 35, 42, 49, 63 and 84 days of ensiling exceeded the values of the ambient temperature, characterizing the heating of the silage during storage. The pre-dried silage of Tifton 85 grass wrapped with two and three layers of polyethylene film had their aerobic stability and fermentation profile damaged during storage and shortages of silos, therefore the silage obtained cannot be considered of good quality